2016
DOI: 10.1186/s13018-016-0403-0
|View full text |Cite
|
Sign up to set email alerts
|

Clinical analysis of preoperative risk factors for the incidence of deep venous thromboembolism in patients undergoing posterior lumbar interbody fusion

Abstract: BackgroundThe purpose of this study aimed to assess preoperative risk factors for the incidence of deep venous thromboembolism in patients undergoing posterior lumbar interbody fusion (PLIF).MethodsThe diagnosis of preoperative deep vein thrombosis (DVT) was confirmed by Doppler ultrasonography. To examine the preoperative risk factors for DVT admitted for PLIF, comparative analysis of the DVT-positive and DVT-negative groups was done.ResultsDVT was detected in 9.4 % (269/2861) patients, including 17 proximal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 20 publications
0
25
2
Order By: Relevance
“…A higher DVT development frequency among hypertensive patients (41.7%) was observed by other research ( 16 ). On the other hand, the findings of the current study were higher than the results reported by ( 17 ) who found that DVT frequency among the participating hypertensive patients was only 9.1% and ( 18 ) who reported that 9.3% of hypertensive patients developed DVT. According to the results of the present study, no significant association was observed between old age and gender and the development of DVT among the studied patients.…”
Section: Discussioncontrasting
confidence: 98%
See 1 more Smart Citation
“…A higher DVT development frequency among hypertensive patients (41.7%) was observed by other research ( 16 ). On the other hand, the findings of the current study were higher than the results reported by ( 17 ) who found that DVT frequency among the participating hypertensive patients was only 9.1% and ( 18 ) who reported that 9.3% of hypertensive patients developed DVT. According to the results of the present study, no significant association was observed between old age and gender and the development of DVT among the studied patients.…”
Section: Discussioncontrasting
confidence: 98%
“…These findings are in line with what was reported by ( 16 , 18 , 23 , 24 ) where these comorbidities had no significant effect on DVT development in the studied population. Furthermore, another study conducted by ( 17 , 26 ) found that diabetes and ischemic heart diseases were not significantly associated with the occurrence of DVT. On the other hand, ( 27 ) viewed a significant association between heart diseases and myocardial infarction and the risk of venous thromboembolism and ( 26 ) clarified a significant association between cancer and DVT.…”
Section: Discussionmentioning
confidence: 92%
“…It is possible that good disease control in RA patients undergoing arthroplasty explains their relatively low VTE risk. In contrast, a recent retrospective study of patients undergoing spine surgery demonstrated a significantly higher risk of VTE in RA patients than non-RA patients [87]. Although this finding requires validation, it could also reflect the more urgent nature of spine surgery, which may not permit RA disease optimization.…”
Section: Venous Thromboembolismcontrasting
confidence: 45%
“…This was not in accordance with the results reported by ( 14 , 16 18 ), where these comorbidities had no significant effect on DVT development in the studied population. Furthermore, another study conducted by ( 19 , 20 ) found that diabetes and ischemic heart diseases were not significantly associated with the occurrence of DVT. Also, another study reported that diabetes mellitus and hypertension were not participated as risk factors ( 21 ).…”
Section: Discussionmentioning
confidence: 92%